2012
DOI: 10.7314/apjcp.2012.13.3.833
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Esophageal Cancer in Kazakhstan

Abstract: The incidence of esophageal cancer in Kazakhstan was analysed for the period of 1989-2010 years, with a focus on trends by age, gender and region. The highest rates of incidence were evident in the Western regions. The dynamics for cancer of the esophagus in the Republic demonstrated decrease, except in the Karaganda region, where a tendency for increase was noted. Considerable variation between regions pointed to differences in risk factor exposure which need to be targeted for future control efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…This might be partly due to the prevalence of Russian ethnicity in these provinces, given the ethnic differential in incidence rates (Igissinov et al, 2013). In contrast, esophageal cancer appears most frequent in the West of the country (Igissinov et al, 2012a) and cervical cancer in the northern half (Igissinov et al, 2012b).…”
Section: Discussionmentioning
confidence: 98%
“…This might be partly due to the prevalence of Russian ethnicity in these provinces, given the ethnic differential in incidence rates (Igissinov et al, 2013). In contrast, esophageal cancer appears most frequent in the West of the country (Igissinov et al, 2012a) and cervical cancer in the northern half (Igissinov et al, 2012b).…”
Section: Discussionmentioning
confidence: 98%
“…In Kazakhstan, it has already been shown that there is geographical variation in incidences of breast (Bilyalova et al, 2012), esophageal (Igissinov S et al, 2012;2013), and cervical cancer , with changes dover time (Igissinov et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Так, в 1989 г. уровень заболеваемости составил 15,50/0000, в то время как в 2010 г. -11,30/0000 [6,7].…”
Section: Introductionunclassified